Conserving the Critically Endangered tree Vatica cauliflora: population and conservation status assessment. Issue 4 (2nd July 2021) - Robiansyah, Iyan; Primananda, Enggal; Rinandio, Dipta Sumeru; Linsky, Jean
Abstract: Vatica cauliflora P.S. Ashton (Dipterocarpaceae) is a threatened tree species endemic to Kapuas Hulu District, West Kalimantan Province, Indonesia. The species is only known from the type specimen collected in 1953. After this first collection, there was no record confirming the presence of this tree in its natural habitat. Our recent surveys in 2019 and 2020 located 179 individuals of the species in six unprotected locations. The population's size structure is dominated (62.6%) by young individuals within the 0–5 cm diameter class. Our surveys also showed that the habitat of V. cauliflora is degraded as a result of the negative effects of agriculture and logging. Assessment with the IUCN Red List criteria indicates that V. cauliflora should be categorized as Critically Endangered.